The maize transcription factor EREB58 mediates the jasmonate‐induced production of sesquiterpene volatiles. (October 2015) - Li, Shengyan; Wang, Hai; Li, Fengqi; Chen, Zhongliang; Li, Xiuying; Zhu, Li; Wang, Guirong; Yu, Jingjuan; Huang, Dafang; Lang, Zhihong
Summary Over the past two decades, Zea mays (maize) has been established as a model system for the study of indirect plant defense against herbivores. When attacked by lepidopteran larvae, maize leaves emit a complex blend of volatiles, mainly composed of sesquiterpenes, to attract the natural enemies of the herbivores. This is associated with a swift transcriptional induction of terpene synthases such as TPS10; however, the molecular components controlling the complex transcriptional reprogramming in this process are still obscure. Here, by exploiting the finding that the maize TPS10 promoter retained its full responsiveness to herbivory in Arabidopsis, we identified the region from −300 to −200 of the TPS10 promoter as both necessary and sufficient for its herbivore inducibility through 5′ deletion mapping. A high‐throughput screening of an Arabidopsis transcription factor library using this promoter region as the bait identified seven AP2/ERF family transcription factors. Among their close homologs in maize, EREB58 was the only gene responsive to herbivory, with a spatiotemporal expression pattern highly similar to that of TPS10. Meanwhile, EREB58 was also responsive to Jasmonate. In vivo and in vitro assays indicated that EREB58 promotes TPS10 expression by directly binding to the GCC‐box within the region from −300 to −200 of the TPS10 promoter. Transgenic maize plants overexpressing EREB58 constitutively over‐accumulate TPS10 transcript, and also (E)‐β‐farnesene and (E)‐α‐bergamotene, two major sesquiterpenes produced by TPS10. In contrast, jasmonate induction of TPS10 and its volatiles was abolished in EREB58‐RNAi transgenic lines. In sum, these results demonstrate that EREB58 is a positive regulator of sesquiterpene production by directly promoting TPS10 expression.